Social Exclusive of Education Inequality in the Covid-19 Pandemia by Education Digitalization Activities - Sarah, Nursani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The process of utilizing digital systems in the world of education to realize a learning process is the government's effort to equalize access to education and reduce the digital divide. The Covid-19 pandemic is to blame for adopting digitalization in the education sector. Using the perspective of social exclusion in Indonesia, this study aims to describe educational inequality through efforts to digitalize education during the Covid-19 pandemic. The literature review method was used to map the issue of social exclusion and inequality in the education sector in Indonesia's digitalization efforts by the government for students. The Google Scholar and Scopus features filter journal articles about educational inequality and digitalization efforts during the data collection process. Based on research findings, building more ICT infrastructure to support 5G in rural developing countries, promoting digital literacy programs, implementing policy incentives for digital technology, and increasing the equity of digital services are all strategic efforts to address educational inequality. Acknowledging comprehensive schooling, The Service of Instruction and Culture sent off a few developments to help the digitalization cycle. The development of a Learning House is one of the most significant.